(untitled) - Blass, Friedrich; (1843-1907) (U.S.A, 1961)
This grammar sets the Greek of the New Testament in the context of Hellenistic Greek and compares and contrasts it with the classical norms. It relates to the New Testament language to its Semitic background, to Greek dialects, and to Latin and has been kept fully abreast of latest developments and manuscript discoveries. It is at no point exclusively dependent on modern editions of the Greek New Testament text but considers variant readings wherever they are significant. It is designed to compress the greatest amount of information into the smallest amount of space consistent with clarity. There are subsections discussing difficult or disputed points and copious citations of primary texts in addition to generous bibliographies for those who wish to pursue specific items further.
Keywords: Greek language, Biblical -- Grammar